Firmare un documento quando non si può scrivere: le croci come sostitute di ‘firme’ autografe nei documenti greci su papiro dell’Egitto bizantino (secoli VI-VII) - Monte, Anna (Scrineum, 2023)
This paper analyses the practice of signing documents with a series of three crosses, which is attested in Greek and Coptic papyri from the sixth century onwards. According to the usual scheme, the crosses are marked by the term σημεῖον ‘sign’ and the name of the signatory written respectively above and below the signs. A subscription written by a third party usually makes it clear that the signatory, although unable to write, signed the document by drawing his σημεῖον. The paper discusses a) the standard structure and variations of this type of signature, b) its spatial and temporal distribution, c) its origin and development, and d) the context in which it was used.